THE INFLUENCE OF LEADERSHIP STYLE, WORK ENVIRONMENT AND WORK DISCIPLINE ON EMPLOYEE PERFORMANCE WITH ORGANIZATIONAL CULTURE AS A VARIABLE INTERVENING IN THE MANPOWER AND TRANSMIGRATION OFFICE OF RIAU ISLANDS PROVINCE MANPOWER SUPERVISION UPT BATAM CITY - Ali Sarpudin; Chablullah Wibisono; Muammar Khaddafi; Bambang Satriawan; Ngaliman; Muhammad Gita Indrawan (RADJA PUBLIKA, 2023)
This research aims to examine the following five variables Leadership style, work environment, work discipline, employee performance and organizational culture Data analysis with parametric and non-parametric statistics using SEM-PLS (Structural Equation Modeling-Partial Least Square) Data analysis with parametric and non-parametric statistics parametric research variables, calibration tests / pilot tests, validity and reliability, outer model and inner model analysis, as well as discussion of the results of hypothesis testing or path analysis. This research uses path analysis to test relationship patterns that reveal the influence of a variable or set of variables on other variables, both direct and indirect influences. The path coefficient calculation in this research was assisted by SmartPLS. From the test results it was found that Leadership Style has a significant positive influence on organizational culture, Work environment has a significant positive influence on organizational culture, Work discipline has a significant positive influence on organizational culture, Leadership Style has a significant positive influence on Employee Performance, Environment Work has a positive but not significant influence on Employee Performance, Work Discipline has a positive but not significant influence on Employee Performance, Organizational culture has a significant positive influence on Employee Performance, There is a significant influence between leadership style on Employee Performance and Organizational Culture as a variable intervening, There is a significant influence between the work environment on Employee Performance and Organizational Culture as an intervening variable. There is a significant influence between work discipline on Employee Performance and Organizational Culture as an intervening variable.